Experimental tests of steel fibre reinforced concrete beams under drop-weight impacts - Hao, Y.; Hao, Hong; Chen, G. (Trans Tech Publications Ltd, 2015)
Concrete is a brittle material, especially under tension. Intensive researches have been reported to add various types of fibres into concrete mix to increase its ductility. Recently, the authors proposed a new type of steel fibre with spiral shape to reinforce concrete material. Laboratory tests on concrete cylinder specimens demonstrated that compared to other fibre types such as the hooked-end, deformed and corrugated fibres the new fibres have larger displacement capacity and provide better bonding with the concrete. This study performs drop-weight impact tests to investigate the behaviour of concrete beams reinforced by different types of steel fibres. The quasi-static compressive and split tensile tests were also conducted to obtain the static properties of plain concrete and steel fibre reinforced concrete (FRC) materials. The quasi-static tests were carried out using hydraulic testing machine and the impact tests were conducted using an instrumented drop-weight testing system. Plain concrete and concrete reinforced by the commonly used hooked-end steel fibres and the proposed spiral-shaped steel fibres were tested in this study. The volume dosage of 1% fibre was used to prepare all FRC specimens. Repeated drop-weight impacts were applied to the beam specimens until total collapse. A 15.2 kg hard steel was used as the drop-weight impactor. A drop height of 0.5 m was considered in performing the impact tests. The force-displacement relations and the energy absorption capabilities of plain concrete and FRC beams were obtained, compared and discussed. The advantage and effectiveness of the newly proposed spiral-shaped steel fibres in increasing the performance of FRC beam elements under impact loads were examined.